The Influence of Transformational Leadership Style, Communication and Work Environment on Employee Performance at PT. Adira Dynamics Multi Finance in Jakarta - Afaf Nahlati Shovi; Ahmad Cik; Adam Nurkholik; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2023)
The purpose of this study is to analyze is there is an influence of Transformational Leadership Style, Communications, and Work Environment on Employee Performance. The data used in this research is using primary data. Data collection techniques were carried out using questionnaires obtained by distributing questionnaires via google form to 56 employees of PT. Adira Dinamika Multi Finance in Jakarta. The data analysis technique used in this research is multiple linear regression analysis, which is processed through the SPSS version 25 program. The data analysis technique used is a quantitative method where the results are expressed by numbers. Based on research that has been done shows that Transformational Leadership Style has a positive and significant effect on employee performance, Communication has a negative and insignificant effect on employee performance, Work Environment has a positive and significant effect on employee’s performance.